The Role of Islamic Non-Governmental Organizations in Environmental Conservation: A Case Study of the Global Muslim Climate Network (GMCN) - Aina, Qurratul; Fauzi, Fauzi; Novialdi, Risky (Universitas Lampung, 2024)
In the international arena, the author believes that one way to maintain world peace is by protecting the environment. In this context, the author posits that actions taken by the Global Muslim Climate Network (GMCN) are instrumental in environmental protection. The GMCN was established in response to the climate challenges faced by predominantly Muslim countries. Composed of scholars, philanthropists, experts, and NGOs, the organization aims to address the climate crisis through the lens of Islamic teachings. GMCN promotes renewable energy and sustainable investment, urging predominantly Muslim countries to increase their renewable energy usage to at least 20% of their energy mix. The organization’s involvement in international environmental diplomacy, advocacy at UN climate conferences, and local initiatives exemplifies its role in shaping global environmental policy. Through collaborative efforts, GMCN demonstrates how Islamic principles can drive innovative solutions to the current environmental crisis, highlighting the potential of religion as a powerful force for global sustainability.Keywords: NGO; Green Diplomacy; GMCN; Environmental Preservation; Islam